Unlocking weather observations at the end of theworld : late XIX and early XX century monthly mean temperatura climatology for Southern Patagonia - Canziani, Pablo O. (2024)
Fil: Canziani, Pablo O. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina